MEMBERDAYAKAN PROGRAM STUDI ILMU KOMUNIKASI - Bayquni, Bayquni (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2009)
By communication human can live their life. communication human can socialization. By human can make and develop their culture. But, by that kind of communication. can we do professional, when Department. of Communication as cm intermediate scholar and this field can be accomplish by another subject of science? Do curriculum of Communication Department over a barrel or its own and what is the weakness of curriculum that applied in Communication Department? This paper tried to explain the content of curriculum indeed by Communication Department.